The Application of Problem Based Learning Model Integrated Guided Inqury Model Using Computer Based Media on Salt Hydrolysis Learning for High School Students Improve Learning Outcomes Class XI Science in Medan - Eva Fadillah; Ramlan Silaban; Iis Siti Jahro (Pascasarjana Universitas Negeri Medan, 2016)
Abstract. This study aims to analyze (1) Differences in chemistry learning outcome of students who got a learning model of Direct Instruction (DI), Problem Based Learning (PBL) Integrated Guided Inquiry (GI), and Problem Based Learning (PBL) Integrated Guided Inquiry (GI) using a computer-based media. This research is experimental. The population is all high school students of class XI in the city of Medan in Academic Year 2013/2014. The sampling technique using cluster random sampling, namely SMAN 4, SMAN 14 and SMAN 21 Medan respectively of 3 classes. The research instrument in the form of test results to learn chemistry and observation sheet student character. The data analysis technique used is the analysis of variance (ANOVA) one direction (one way ANOVA) with SPSS 20 for windows at significance level α = 0.05. Based on the results of data processing, is obtained that (1) There are differences in learning outcomes between students who received the chemistry applied learning models. Keywords: PBL, GI and DI, learning outcomes, character